Accuracy of Femoral Tunnel Placement in Medial Patellofemoral Ligament Reconstruction: The Effect of a Nearly True-Lateral Fluoroscopic View. (September 2015) - Balcarek, Peter; Walde, Tim Alexander
Background: Reconstruction of the medial patellofemoral ligament (MPFL) is an established operative procedure for patients with recurrent episodes of lateral patellar instability. However, recent articles have reported remarkable complication rates, with nonanatomic femoral tunnel positioning in up to 64% of patients. Purpose: To evaluate the sensitivity of femoral tunnel placement using lateral fluoroscopic guidance to minor degrees of deviation from the true-lateral view using established radiographic landmarks. Study Design: Controlled laboratory study. Methods: Six human cadaveric femora were used for this study. A 6-mm radiopaque eyelet was used to mark the native femoral insertion of the MPFL according to previously described radiographic landmarks. Radiographic landmarks were also applied with the femur positioned in 2.5° and 5° of internal and external rotation, respectively, and with the femur in 2.5° and 5° of hip abduction and adduction, respectively. The distance between the center of the 6-mm eyelet to the center of the native femoral MPFL insertion, as established in the true-lateral view, was measured and determined as the degree of shift in each position. Results: Hip adduction, abduction, and internal and external rotations of 2.5° resulted in a shift from the native femoral MPFL insertion point to a more distal (adduction), proximal (abduction), anterior (internal rotation), and posterior location (external rotation) of 2.7 ± 0.7, 2.0 ± 0.7, 2.7 ± 1.1, and 3.0 ± 1.3 mm, respectively (all P < .05). Malpositioning increased to a distance of 5.0 ± 0.7 mm distally, 3.6 ± 1.0 mm proximally, 5.2 ± 0.8 mm anteriorly, and 6.2 ± 0.6 mm posteriorly to the native insertion point when the attachment was marked with 5° of divergence from the true-lateral view (all P < .05). Conclusion: The results of this study indicate the high sensitivity of femoral tunnel placement using lateral fluoroscopic guidance to minor degrees of deviation from the true-lateral view. Clinical Relevance: The study highlights the importance of an exact lateral view when fluoroscopic guidance is used for femoral tunnel positioning in the daily practice of MPFL reconstruction, and a possible explanation for the high incidence of nonanatomic tunnel placement is suggested.